Lung adenocarcinoma with tumor resolution and dystrophic calcification after salvage surgery following immune checkpoint inhibitor therapy: A case report. Issue 11 (15th September 2020) - Sumi, Toshiyuki; Uehara, Hirofumi; Masaoka, Toshiaki; Tada, Makoto; Keira, Yoshiko; Kamada, Koki; Shijubou, Naoki; Yamada, Yuichi; Nakata, Hisashi; Mori, Yuji; Chiba, Hirofumi
Abstract : A clinical trial of immune checkpoint inhibitors for advanced non‐small cell lung cancer reported an overall survival plateau with a long tail to the survival curve, suggesting that immune checkpoint inhibitors prolong survival. However, little evidence supports the efficacy of immune checkpoint inhibitors as neoadjuvant chemotherapy. We performed salvage surgery on a patient who was treated with an anti‐programmed cell death protein‐1 (PD‐1) antibody and whose tumor size had not changed over time. A 69‐year‐old Japanese female with advanced lung adenocarcinoma was initially administered pembrolizumab therapy; however, owing to the development of various immune‐related adverse events (irAEs), the patient was switched to chemotherapy following steroid therapy. The tumor continued to shrink and calcification within the tumor increased. We performed salvage surgery following which the tumor cells disappeared and necrosis and calcification were detected in the tumor. We concluded that if calcification develops within the tumor and tumor shrinkage is maintained after treatment with anti‐PD‐1 drugs, the calcification may be dystrophic owing to drug‐induced tumor necrosis, and salvage surgery might be beneficial in removing the tumor. Key points: Significant findings of the study: If calcification develops within the tumor and tumor shrinkage is maintained after treatment with anti‐PD‐1 drugs, the calcification may be dystrophic owing to tumor necrosis caused by drug effects, and salvage surgery might be beneficial in removing the tumor. What this study adds: This study showed the efficacy of immune checkpoint inhibitors as neoadjuvant chemotherapy to be followed by salvage surgery for unresectable advanced lung adenocarcinoma. Abstract : If calcification develops within the tumor and tumor shrinkage is maintained after treatment with anti‐PD‐1 drugs, the calcification may be dystrophic owing to tumor necrosis caused by drug effects, and salvage surgery might be beneficial in removing the tumor.